中国房地产开发企业资金运行 = Project finance management of China's property development enterprises - 马洪涛 Ma, Hongtao (2008)
This paper studies the finance source and management of property firms in China. Due to small size, the external finance and speedy fund circulation are key factors for the success of developers in China. Through the study of production, marketing and sales and consumption of residential property, we propose some suggestions for the developers to utilize their limited finance more efficiently.